Development of Underdeveloped Regions in Indonesia: Optimizing Natural Resources and Technology for Sustainable Progress - Lasaiba, Mohammad Amin (Universitas Pattimura, 2023)
Developing underdeveloped regions is an important regional development issue requiring special attention. This article discusses the limitations of technology and innovation that often hinder the development of underdeveloped regions. In addition, this article also discusses the potential of natural resources in underdeveloped regions and how their utilization can support regional development. A case study of the development of underdeveloped regions in Indonesia is also discussed to provide an overview of the success and failure of underdeveloped regional development programs and the factors that influence the success of these programs. Overcoming the gap or problem of underdeveloped regional development requires integrated and sustainable efforts between the government, community, and private sectors. These efforts can be carried out through various programs and policies that support the development of human resources, infrastructure improvement, and sustainable utilization of natural resources.